Os impactos socioambientais da Quarta Revolução Industrial: precarização do trabalho e esgotamento da natureza - Pinton, Patricia (2020)
This work is presented since the advent of the Fourth Industrial Revolution, which since the beginning of the 21th century, with overwhelming speed and intensity, radically transforms the way of life of people and the environment itself. In this sense, the aim of the research is to explain and evaluate the socioenvironmental effects fostered by this Industrial Revolution in the face of the current situation, which takes place under the prism of a critical view, linked to the bases of Marxist theory. Thus, the central question that the study proposes to answer is related to “what are and what will be the socio-environmental impacts caused by the so-called Fourth Industrial Revolution, in the face of the current context of Capitalism?” In order to obtain an effective answer, the method used in the investigation is dialectical historical materialism because, in general, the starting point of the research is substantiated in reality, “in the concrete”, seeking to highlight the contradictions of both processes and existence, to return to it and establish a synthesis, outlined as “the concrete thought”. In order to specify the contradictions mentioned, it is sought to point out what looks and what is in the essence of this reality under analysis. That is, how the Fourth Industrial Revolution appears, with its promise of advances and gains for humanity, but that, at the same time, in fact, it conceals consequences that are already proving harmful to those who live off their labor force, as well as nature itself. In the end, the trends of the Fourth Industrial Revolution are pointed out, which inevitably lead to the precariousness of human work and the depletion of natural resources.